PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada Perusahaan yang Terdaftar di NIKKEI 225 dan Jakarta Composite Index Tahun 2018-2021) - Diani, Amadea Arum; Arfinto, Erman Denny; Octavio, Danes Quirira (Diponegoro Journal of Management, 2024)
ABSTRACT This research aims to examine the influence of the intellectual capital component on the company’s financial performance of companies listed on NIKKEI 225 and the Jakarta Composite Index for 2018-2021. The intellectual capital components that are tested include human capital (HCE), structural capital (SCE), relational capital (RCE), innovation capital (RDE), dan capital employed (CEE). This research also looks at the differences in the influence of intellectual capital on companies in Japan and Indonesia. The data used in this research is secondary data originating from the financial reports of companies listed on NIKKEI 225 and Jakarta Composite Index (JCI) during the 2018-2021 period. The required data was obtained from Bloomberg. This research uses multiple regression analysis in the SPSS program. The research results show that HCE and RCE have a significant negative influence on the company’s financial performance, while SCE, RDE, and CEE have a significant positive influence on the company’s financial performance. Apart from that, the difference in the influence of intellectual capital concludes that Japan will have worse ROA performance than Indonesia.